Impact of switching to polypill based therapy by baseline potency of medication: Post-hoc analysis of the SPACE Collaboration dataset. (15th December 2017) - Webster, Ruth; Bullen, Chris; Patel, Anushka; Selak, Vanessa; Stepien, Sandrine; Thom, Simon; Rodgers, Anthony
Abstract: Background: Fixed dose combinations of cardiovascular therapy ('polypills') have now been launched in several dozen countries. There is considerable clinical interest in the effects of switching to polypill-based care from typical current treatment regimens, especially if polypills contain components at sub-maximal dosage. Methods: The SPACE Collaboration includes three trials of polypill based care vs usual care in patients with established CVD or at high calculated risk. Individual patient data for 3140 trial participants were combined. Patients were categorized according to the potency of the statin and the number of BP lowering medications they were taking at baseline. Effects on adherence to anti-platelet medication, systolic blood pressure (SBP) and LDL cholesterol stratified by baseline potency of medication were determined using fixed effects models. Results: Randomisation to the polypill group was associated with improved SBP at 12 months, but this improvement varied according to baseline BP regimen: − 3.3, − 5.9, − 2.5 and + 1 mm Hg for patients taking 0, 1, 2 and 3 + BP lowering medications at baseline. For changes in LDL cholesterol at 12 months, significant improvements in LDL cholesterol were seen for those taking no statin (− 0.21 mmol/L; 95% CI: − 0.34 to − 0.07), less potent statin (− 0.16 mmol/L; 95% CI: − 0.29 to − 0.04) and equipotent statins (− 0.14 mmol/L; 95% CI − 0.26 to − 0.02) at baseline. Conclusion: The adherence benefits of polypills tend to offset the loss of potency from use of individual components with lower dose potency, and to facilitate improvements in multiple risk factors.